The development of the cucullaris muscle and the branchial musculature in the Longnose Gar, (Lepisosteus osseus, Lepisosteiformes, Actinopterygii) and its implications for the evolution and development of the head/trunk interface in vertebrates. Issue 6 (13th October 2017) - Naumann, Benjamin; Warth, Peter; Olsson, Lennart; Konstantinidis, Peter
Abstract : The vertebrate head/trunk interface is the region of the body where the different developmental programs of the head and trunk come in contact. Many anatomical structures that develop in this transition zone differ from similar structures in the head or the trunk. This is best exemplified by the cucullaris/trapezius muscle, spanning the head/trunk interface by connecting the head to the pectoral girdle. The source of this muscle has been claimed to be either the unsegmented head mesoderm or the somites of the trunk. However most recent data on the development of the cucullaris muscle are derived from tetrapods and information from actinopterygian taxa is scarce. We used classical histology in combination with fluorescent whole‐mount antibody staining and micro‐computed tomography to investigate the developmental pattern of the cucullaris and the branchial muscles in a basal actinopterygian, the Longnose gar ( Lepisosteus osseus ). Our results show (1) that the cucullaris has been misidentified in earlier studies on its development in Lepisosteus . (2) Cucullaris development is delayed compared to other head and trunk muscles. (3) This developmental pattern of the cucullaris is similar to that reported from some tetrapod taxa. (4) That the retractor dorsalis muscle of L. osseus shows a delayed developmental pattern similar to the cucullaris. Our data are in agreement with an explanatory scenario for the cucullaris development in tetrapods, suggesting that these mechanisms are conserved throughout the Osteichthyes. Furthermore the developmental pattern of the retractor dorsalis, also spanning the head/trunk interface, seems to be controlled by similar mechanisms.